Budget Institutions and Fiscal Performance in Latin America - Ricardo Hausmann; Alberto Alesina; Rudolf Hommes; Ernesto H. Stein (Inter-American Development Bank, Office of the Chief Economist, 1998)
In this paper detailed information on the budget institutions of Latin American countries is collected. These institutions are classified on a hierarchical/collegial scale, as a function of the existence of constraints on the deficit and voting rules.
Keywords: 330; Öffentliche Schulden; Öffentlicher Haushalt; Finanzpolitik; Finanzverfassung; Institutionalismus; Lateinamerika